Adults with congenital limb deficiency in Norway: demographic and clinical features, pain and the use of health care and welfare services. A cross-sectional study. (23rd October 2015) - Johansen, Heidi; Østlie, Kristin; Andersen, Liv Øinæs; Rand-Hendriksen, Svend
Abstract: Purpose : To describe an adult population with congenital limb deficiency (CLD) recruited through the National Resource Centre for Rare Disorders (TRS) in Norway: (1) demographic factors, (2) clinical features, (3) pain and (4) use of health care and welfare services. Methods : Cross-sectional study. In 2012, a postal questionnaire was sent to 186 eligible persons with CLD, age 20 years and older. Results : Ninety-seven respondents, median-age 39 years (range: 20–82); 71% were women. The population was divided into two subgroups: (1) unilateral upper-limb deficiency (UULD) n  = 77, (2) multiple and/or lower-limb deficiency (MLD/LLD). About 40% worked full-time, 18% received disability pensions and 64% reported chronic pain, mostly bilateral pain. Grip-improving devices were used more often than prostheses; 23% were previous prosthesis users. Use of health care and welfare services are described. No significant differences were found between the subgroups regarding pain or employment status. Conclusions : Persons with CLD reported increased prevalence of chronic pain, mostly bilateral, and increased prevalence of early retirement. A greater focus on the benefits of the use of assistive devices, the consequences of overuse and vocational guidance may moderate pain and prevent early retirement. Further studies of more representative samples should be conducted to confirm our findings. Implications for Rehabilitation: Most adults with congenital limb deficiency (CLD) live ordinary lives and experience normal life events. However, several report chronic pain and retire before normal retirement age. In spite of free and accessible prosthetic services, a large fraction chooses not to use prosthesis, more use grip-improving devices for specific activities. These preferences should be acknowledged by rehabilitation specialists. Focus on individually adapted environments, more information about the consequences of overuse, and vocational guidance may moderate pain and prevent early retirement.